Elaborative Research into the Floral Biology of Bidens pilosa in Sidhi District of Madhya Pradesh, India - Rinkoo Vishwakarma; Mohammad Salim (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The current chapter describes the life cycle of Bidens pilosa throughout the year, including its vegetative, flowering, and fruiting phases. The plant produces different types of flowers called capitula, with ray florets opening on the first day and disc florets opening on the following four days. While ray florets are sterile, disc florets are fertile and exhibit various characteristics such as dichogamy, protandry, herkogamy, self-compatibility, self-pollination through vectors, and the potential for cross-pollination. The disc florets also have a secondary pollen presentation. The plant primarily relies on insects for pollination, but wind and rain can also play a role. The disc florets yield both long and short cypselas (seeds) from the same capitulum. The dispersal of seeds involves multiple methods, including wind, animals, and water.